The Effect of Elevated Alanine Transaminase on Non-invasive Prenatal Screening Failures - Chen, Ping; Qiao, Longwei; Zhang, Sheng; Jin, Jieyu; Cao, Jun; Zhang, Yuqiong; Tang, Haoyu; Yu, Zheng; Shi, Jingye; Yin, JingPing; Liang, Yuting; Wu, Xiao (Frontiers in Medicine, 2022)
Objective To determine the effects of the level of alanine transaminase (ALT) on the rate of screening failures or “no calls” to obtain a result in non-invasive prenatal screening (NIPS). Methods NIPS sequencing and liver enzyme measurements were performed for 7,910 pregnancies at 12-26 weeks of gestation. Univariate and multivariate regression models were used to evaluate the significant predictors of the rate of screening failures among maternal characteristics and relevant laboratory parameters. Results Among 7,910 pregnancies that met the inclusion criteria, 134 (1.69%) had “no calls.” Multiple logistic regression analysis demonstrated that increased body mass index (BMI), ALT, prealbumin (PAB), albumin, and in vitro fertilization (IVF) conception were independently associated with screening failures. The test failure rate was higher (4.34% versus 1.41%; P<0.001) in IVF pregnancies than in spontaneous conceptions. Meanwhile, the rate of screening failures increased with increasing ALT levels from 1.05% at ≤10 U/L to 3.73% at >40 U/L. In particular, IVF pregnancies with ALT >40 U/L had a higher test failure rate (9.52%). Compared with ALT≤10 U/L, the adjusted odds ratio of “no calls” were 1.204 (95% CI, 0.709-2.045) for ALT 10-20 U/L, 1.529 (95% CI, 0.865-2.702) for ALT 21-40 U/L and 2.764 (95% CI, 1.500-5.093) for ALT>40 U/L (Ptrend <0.001). Conclusions Increased ALT and IVF conceptions were associated with a higher screening failures rate in NIPS. Therefore, a feasible strategy to adjust these factors to reduce the probability of “no calls” due to the low fetal fraction (FF) would be of great clinical significance.